2018
DOI: 10.4103/jfmpc.jfmpc_154_17
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and anxiety, stress, and depression in Iranian resident physicians

Abstract: Background:Residency is one of the most critical periods of medical education. Residents are susceptible in high risk for mental problems which can affect the doctor–patient relationship. Emotional intelligence (EI) correlates closely with stress and mental health. Considering the important role of EI in medical education and with regard to lack of studies in this group in Iran, this study conducted to determine the relationship between EI and stress, anxiety, and depression in a sample of resident physician i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 14 publications
5
26
0
5
Order By: Relevance
“…Emotional intelligence level is negatively correlated with anxiety, depression and stress. This had been confirmed in several studies (Cejudo et al, 2018; Kousha et al, 2018; Nolidin et al, 2013). In a study of twin women's prenatal anxiety and depression, Fu said (Fu et al, 2020) under anxiety, depression and stress, high EI might be more likely to recognise negative emotions.…”
Section: Introductionsupporting
confidence: 52%
“…Emotional intelligence level is negatively correlated with anxiety, depression and stress. This had been confirmed in several studies (Cejudo et al, 2018; Kousha et al, 2018; Nolidin et al, 2013). In a study of twin women's prenatal anxiety and depression, Fu said (Fu et al, 2020) under anxiety, depression and stress, high EI might be more likely to recognise negative emotions.…”
Section: Introductionsupporting
confidence: 52%
“…Dalam proses pembelajarannya banyak mahasiswa baru merasa penuh dengan tuntutan, adanya kebutuhan untuk belajar terus-menerus, tanggung jawab yang berlebihan dan kurangnya waktu untuk istirahat. (Kousha, Bagheri and Heydarzadeh, 2018). Rutinitas yang sering terjadi dalam kehidupan mahasiswa kedokteran adalah tidur yang tidak mencukupi, jam kuliah yang melelahkan, beban keuangan, lingkungan yang tidak mendukung dan faktor sosial lainnya (Onyishi et al, 2016).…”
Section: Pendahuluanunclassified
“…Mahasiswa baru ini mengalami masa transisi, mereka mencoba menyesuaikan diri, mempertahankan nilai yang bagus, merencanakan masa depan dan berada jauh dari rumah yang sering menyebabkan kecemasan yang berujung pada depresi (Sarokhani, 2013).Dalam proses pembelajarannya banyak mahasiswa baru merasa penuh dengan tuntutan, adanya kebutuhan untuk belajar terus-menerus, tanggung jawab yang berlebihan dan kurangnya waktu untuk istirahat. (Kousha, Bagheri and Heydarzadeh, 2018). Rutinitas yang sering terjadi dalam kehidupan mahasiswa kedokteran adalah tidur yang tidak mencukupi, jam kuliah yang melelahkan, beban keuangan, lingkungan yang tidak mendukung dan faktor sosial lainnya (Onyishi et al, 2016).…”
unclassified
“…The mental health risk could be assessed through level of depression, anxiety, and stress as these three forms the fundamentals of mental health problems, which is evident from the literature aforementioned (APA, 2013; Lee et al, 2019;McHugh et al, 2020). The literature support also demonstrates that the factors like transpersonal gratitude, emotional intelligence, and life contentment could help reduce depression, anxiety, and stress (Chowdhury, 2020;Ghazwin et al, 2016;Kousha et al, 2018).…”
Section: Significancementioning
confidence: 99%
“…Also, it has been found that emotional intelligence; the ability to understand and manage one's emotions and of others around us (Salovey & Mayer, 1990;Schutte et al, 1998), is associated with transpersonal gratitude such that higher the gratitude higher the emotional intelligence (Geng, 2018). The higher emotional intelligence leads to decrease depression, anxiety, and stress (Davis & Humphray, 2012;Kim et al, 2017;Kousha et al, 2018;Tannous & Matar, 2010). The third variable of study interest is life contentment.…”
Section: Introductionmentioning
confidence: 99%